2003
DOI: 10.1248/bpb.26.1342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory Activity of Chloroform Extract of Bryonia laciniosa in Experimental Animal Models

Abstract: The anti-inflammatory effect of the leaves of Bryonia laciniosa was evaluated using carrageenan, dextran, histamine, serotonin induced rat paw oedema and cotton pellet induced granuloma (chronic) models in rats. In mice, carrageenan peritonitis test was performed for the extract by oral administration. The chloroform extract of Bryonia laciniosa (CEBL) exhibited significant anti-inflammatory effect at the dose 50, 100 and 200 mg/kg. Maximum inhibition (52.4%) was noted at the dose of 200 mg/kg after 3 h of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 8 publications
0
29
0
1
Order By: Relevance
“…30) The cotton pellet granuloma method is a suitable test for assessing the antiin‰ammatory activity drugs and widely used to evaluate the transudative and proliferative components of chronic in‰ammation. 31) Our results showed that the methanol extracts of EM and EB signiˆcantly inhibited the growth of granuloma tissue in a nondosedependent manner. On the contrary, AB showed little eŠect on reducing the weight of granuloma.…”
Section: Discussionmentioning
confidence: 53%
“…30) The cotton pellet granuloma method is a suitable test for assessing the antiin‰ammatory activity drugs and widely used to evaluate the transudative and proliferative components of chronic in‰ammation. 31) Our results showed that the methanol extracts of EM and EB signiˆcantly inhibited the growth of granuloma tissue in a nondosedependent manner. On the contrary, AB showed little eŠect on reducing the weight of granuloma.…”
Section: Discussionmentioning
confidence: 53%
“…This test was used for initial screening to select the best dose (50 mg/kg) for the other tests of anti-inflammatory activity. Indomethacin was chosen as a positive control because it is a very effective antiinflammatory nonsteroidal drug that is widely used in the literature (Gupta et al, 2003;Tunalier et al, 2007).…”
Section: Thioglycolate Induced Peritonitismentioning
confidence: 99%
“…The Cotton pellets-induced granuloma test was performed according to the method of Gupta et al (2003). The rats were divided into five groups (n = 6).…”
Section: Cotton Pellets-induced Granulomamentioning
confidence: 99%